DISSECTING PROCEDURAL JUSTICE: INDONESIAN AND THAI LEGAL POLICIES TOWARDS FEMALE RAPE VICTIMS WHO CHOOSE ABORTION - Sri Jayanti Sirait; Atikah Rahmi (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
The practice of abortion, particularly that resulting from rape, is a complex legal, health, and human rights issue in Indonesia and Thailand. Female victims of rape often experience unwanted pregnancies, which can have serious physical, psychological, and social consequences, potentially leading to illegal abortions that endanger lives. This study aims to analyze and compare the Indonesian and Thai criminal justice systems in handling abortions resulting from rape, with an emphasis on legal protection for female victims of sexual violence. The method used is a normative juridical approach with a comparative legal study, through analysis of legislation, court decisions, empirical data, and international reports. The results of the study indicate that Indonesia still applies a dualistic approach between the criminalization of abortion and limited exceptions under the Health Law, which in practice creates legal uncertainty and has the potential to lead to re-victimization of victims. In contrast, Thailand applies a more progressive approach by separating abortion as a health issue and rape as a criminal offense, and positions women as victims in need of protection and recovery, rather than as subjects of punishment. This comparison indicates that the Thai legal system is more responsive to the protection of women's reproductive rights and the prevention of re-victimization. Therefore, legal reform and harmonization are needed in Indonesia so that the handling of abortions resulting from rape is more oriented towards justice, victim protection, and women's reproductive health.